On the Activity of Bodies of National Self-Government of the Crimean Tatar People in 1919 and the Problem of Dating the Crimean Tatar Revolution - Andrii Ivanets (Українознавство, 2019)
The article discusses the concept of the Crimean Tatar Revolution, which began in 1917; the problem of determining its upper chronological boundary; and the activities of the Crimean Tatar national authorities in 1919. As a result of the Russian Empire’s policy, in the early 20th century the Crimean Tatar people faced dramatic challenges in the sociopolitical, socioeconomic and ethnodemographic spheres: in their historical homeland, in Crimea, they became a repressed minority, threatened by degradation and assimilation. The 1917 revolutionary events in Russia gave a chance, used by the Crimean Tatar representatives. At that time, the new national elite, formed, first of all, from the nation’s intelligentsia, moved the old leading strata (murza and clergy), facilitated the mobilization of the masses around the ideas of national self-organization and the realization of the right for self-determination. The starting point of the Crimean Tatar Revolution was the holding in December 1917 of the Crimean Tatar constituent assembly – Kurultai – which approved the National Constitution, put forward the idea of creating the Crimean People’s Republic, and became the national parliament for a period of one year. In 1918, it worked under the difficult conditions of shifting political regimes in Crimea. In early 1919, during the confrontation with the Crimean Provincial Government of S. Kryma and the Volunteer Army, elections were held for a new convocation of the parliament – Majlis Mebusan, which briefly worked in March. At the same time, much attention was paid to the Crimean Tatars’ national self-government bodies in the election campaign of the Crimean Sejm, but the capture of Crimea by the Red Army in April 1919 made it impossible to hold elections. The left-radical regime led by the Bolsheviks in Crimea, proclaimed in the spring of 1919 by the Crimean Soviet Socialist Republic, did not last long, but it did show intentions to take into account the Crimean Tatar factor. The dictatorial regime of A. Denikin, who established control over Crimea in the summer of 1919, pursued repressive policies against the Crimean Tatar authorities. According to the author, the violent cessation of self-government in August 1919 marked the end of the Crimean Tatar National Revolution.